Project planning and management : a guide for nurses and interprofessional teams - Harris, James L.; Roussel, Linda; Thomas, Patricia L.; Dearman, Catherine (2020)
"Project Planning and Management: A Guide for Nurses and Interprofessional Teams, Third Edition serves as a primary resource for students developing and implementing clinical projects as a requirement for course completion. Additionally, the text also serves as a guide for faculty and preceptors who assist students in identifying clinical and management gaps as well as in initiating projects.The Third Edition focuses on planning and managing evidence-based projects, phases of implementation, and evaluation methods within the context of quality, safety, and value-based initiatives. Coverage of the expanded use of technology and the importance of designing project/program plans with explicit tools and tactics for success will also be outlined. A central theme woven throughout the text is the impact of outcomes that engage and inspire through dynamic projects. Readers of this text will also benefit from the real-world examples drawn from students, faculty, clinician, manager, and administrator experiences"--
Includes bibliographical references and index.
Keywords: Nursing; Clinical Nursing Research; Program Development; Planning Techniques; Interprofessional Relations